A degree of dispersion‐based damage localization method. Issue 1 (4th June 2015) - An, Yonghui; Błachowski, Bartłomiej; Ou, Jinping
Summary: We present an efficient and robust damage localization method. Its applications therefore include defect location in shear buildings and beam structures. The proposed method is based on the knowledge of the difference of curvatures, computed for a structure before and after damage occurs. However, instead of using modal shapes for this purpose, as is frequently performed, the present method computes the curvature directly from acceleration signals, without identifying modal shapes of the structure. Additionally, the accelerations are subjected to averaging, which reduces measurement noise, and logarithm extraction, which renders the method independent of the amplitude of the loading impulse used for damage location. Another important feature of the method is that it does not require any calibration of numerical models, because it is solely based on measurement data. The presented method of damage location is illustrated with two examples, which involve experimental tests on laboratory‐scale structures. The first example concerns defect location in a shear‐building structure, and the second one in a spatially excited simply supported steel beam. Both cases confirm the effectiveness of the method, and its robustness to measurement noise. Copyright © 2015 John Wiley & Sons, Ltd.